Pola Pembelajaran Nilai-Nilai Kehidupan dalam Keluarga - Muhammad Jailani; Nurjanah Nurjanah (Prodi Pendidikan Keagamaan Islam, 2022)
The progress of a country does not depend on the age of the country. The progress of a country depends on a positive attitude towards life, namely integrity, responsibility, honesty, respect for regulations and other people, working hard, empathy, honesty, and discipline. The purpose of this study is that character education is an important thing that is a necessity for the Indonesian people to cultivate virtue values ​​and eliminate the negative culture that is increasingly mushrooming. Character education can be said as a subjective assessment of a person against others on mental and moral qualities or relating to personality attributes that are accepted by society. This type of research is qualitative research. Qualitative research is essentially observing people in their environment, interacting with them, and trying to understand their language and interpretation of the world around them. The results of this study found that children are a mandate entrusted by Allah SWT to their parents. Children have hearts that are still pure, clean from all patterns and colors, and are ready to be molded to be made into anything depending on the wishes of the former.